Development and validation of a UPLC-MS/MS method with volumetric absorptive microsampling to quantitate cyclophosphamide and 4-hydroxycyclophosphamide - Harahap, Yahdiana; Steven, Steven; Suryadi, Herman (Frontiers in Pharmacology, 2022)
Cyclophosphamide (CP) is an anticancer alkylating prodrug, metabolized by CYP450 into its active metabolite, 4-hydroxycyclophosphamide (4-OHCP). Its therapeutic effectiveness is determined by the 4-OHCP concentration. Several analytical methods in plasma and Dried Blood Spot have been developed to analyze cyclophosphamide and 4-OHCP, however, there are many disadvantages. The objective of this study was to develop and validate ultra-high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method using volumetric absorptive microsampling (VAMS) 4-hydroxycyclophosphamide-d4 (4-OHCP-d4) as an internal standard. VAMS requires small sample volumes, it is not affected by the hematocrit values, therefore, it is an efficient sampling method. Samples were derivatized with 5 μL semicarbazide hydrochloride (SCZ) and 25 µL of the resulting 4-OHCP-SCZ, 4-OHCP-d4-SCZ derivatives were absorbed by VAMS and extracted by protein precipitation. The optimum conditions were obtained using the Waters Acquity® UPLC BEH C18 (2.1 x 100 mm; 1.7 µm) column; flow rate 0.15 mL/min; mobile phase 0.01% formic acid and methanol; gradient elution mode for six minutes using positive electrospray ionization and multiple reaction monitoring of m/z 260.7>140.0 for CP, 333.7>221.0 for 4-OHCP-SCZ, and 337.7>225.1 for 4-OHCP-d4-SCZ. The method has met the validation requirements set by the FDA (2018). Cyclophosphamide LLOQ value was 5 ng/mL and the calibration curve range was 5 - 60,000 ng/mL. Furthermore, the 4-OHCP LLOQ value was 2.5 ng/mL, and the calibration curve range was 2.5 - 1,000 ng/mL.